Exploration of Ethnomathematics in Traditional Lebaran Food in Labuhanbatu - Kartika, Siska Yuli (JMEA : Journal of Mathematics Education and Application, 2024)
This study aims to explore the potential of ethnomathematics in the concept of solid geometry contained in traditional Lebaran foods in Labuhanbatu. The research was conducted using a qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that traditional Lebaran foods in Labuhanbatu contain various solid geometry concepts, such as cylinders, rhombic prisms, spheres, and blocks. These solid geometry concepts are closely related to the process of making traditional Lebaran foods, both in the form of the ingredients used and in the manufacturing process. Additionally, traditional Lebaran foods also contain ethnomathematical values reflected in the patterns, motifs, and shapes found in these foods. Based on this research, it can be concluded that traditional Lebaran foods in Labuhanbatu can be a potential learning resource for teaching solid geometry concepts in mathematics education. Exploring ethnomathematics in traditional Lebaran foods can help students understand solid geometry concepts contextually, thus increasing students' interest and motivation in learning. Therefore, it is hoped that the results of this research can contribute to the development of contextual and culturally-based mathematics education in Indonesia.Key Words: Exploration, Ethnomathematics, Solid Geometry, Lebaran, Mathematics Learning.